As comunidades tradicionais e a discussão sobre o conceito de território - de Moraes, Nelson Russo [UNESP]; Campos, Alexandre de Castro [UNESP]; Müller, Neuza de Moraes [UNESP]; Gamba, Fábio Brega; Gamba, Maria Fernanda Dantas di Flora (My University, 2017)
The development of a society goes through the articulation of trails that lead to the sustainability of their communities, in the interim the traditional features interfere with the characterization of social groups, bringing up new issues that become cross to contemporary debates development communities, especially traditional. Thus, the territory goes beyond the nationalist and even geographical definitions for a range of human, historical and cultural correlations. This scientific article, in the unfolding of the research Analysis of the third sector as a way to develop communities, institutionalized by UNESP and relying on external research partnerships, scientifically announces exploratory research theoretical basis that preceded the field work, especially in search contemporary coinage of the term territory.
Keywords: Territory; Third sector; Traditional communities